Description of a new species of Ameroseius Berlese (Acari: Ameroseiidae) from Norway, with a key to related species - Narita, João Paulo Z.; Abduch, William Y.; Moraes, Gilberto J. De; Klingen, Ingeborg (Zootaxa, 2015)
Ameroseius is the largest genus of the mite family Ameroseiidae (Mesostigmata), with a worldwide distribution. Ameroseius norvegicus Narita, Abduch & Moraes n. sp. is described based on the morphology of adult females collected from litter in a strawberry field, in Norway. The new species is most similar to Ameroseius ulmi Hirschmann. A key is provided to separate them as well as other similar species constituting what is here referred to as the sculptilis group.